Masters porcelain: major works by leading ceramists - Burkett, Richard; Tourtillott, Suzanne J. E. (Lark Books, 2008)
Porcelain--prized for its unique qualities of pristine whiteness, strength, and texture--is an unusual and notoriously difficult clay whose very definition remains subject to debate. The 40 sculptors and potters who have been chosen by Richard Burkett to appear in this curated collection expand and challenge traditional perceptions of what the medium can--and should--do. Their work represents the great diversity in practice--both technical and aesthetic--that porcelain affords the ceramists who mine its tremendous potential.